2023
DOI: 10.1242/jeb.245289
|View full text |Cite
|
Sign up to set email alerts
|

Displacement experiments provide evidence for path integration in Drosophila

Abstract: Like many other animals, insects are capable of returning to previously visited locations using path integration, a memory of travelled direction and distance. Recent studies suggest that also Drosophila can use path integration to return to a food reward. However, the existing experimental evidence for path integration in Drosophila has a potential confound: pheromones deposited at the site of reward might enable flies to find previously rewarding locations even without memory. Here we show that pheromones in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…We took advantage of a published dataset (Corfas et al, 2019), where starved flies were stimulated for 1 s by optogenetically activating neurons expressing sweet gustatory receptors (Miyamoto and Amrein, 2014; Miyamoto et al, 2012) whenever they reached a restricted area in the center of a walking arena. In this assay, flies responded with a search around the site of stimulation, which we will term “optogenetic search” (Kim and Dickinson, 2017; Titova et al, 2023). To evaluate which features were shared between real food-induced local search and optogenetic search, we segmented and analyzed trajectories from flies that were stimulated by activating neurons targeted by a Gr43a- and Gr5a-Gal4 line (Corfas et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We took advantage of a published dataset (Corfas et al, 2019), where starved flies were stimulated for 1 s by optogenetically activating neurons expressing sweet gustatory receptors (Miyamoto and Amrein, 2014; Miyamoto et al, 2012) whenever they reached a restricted area in the center of a walking arena. In this assay, flies responded with a search around the site of stimulation, which we will term “optogenetic search” (Kim and Dickinson, 2017; Titova et al, 2023). To evaluate which features were shared between real food-induced local search and optogenetic search, we segmented and analyzed trajectories from flies that were stimulated by activating neurons targeted by a Gr43a- and Gr5a-Gal4 line (Corfas et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Because locomotor adjustments alone cannot explain the larger scale search pattern with persistent returns, we concluded that flies searching for food in the dark used additional strategies to return to the food. It has been suggested that flies use path integration to keep track of the food spot location (Behbahani et al, 2021; Corfas et al, 2019; Kim and Dickinson, 2017; Titova et al, 2023). A common assumption is that the insect head direction (HD) system (Seelig and Jayaraman, 2015) is required for path integration (Heinze et al, 2018; Stone et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations